Lembaga Pemberdayaan Masyarakat Rumah Kupas Sebagai Solusi Permasalahan Masyarakat Pesisir Karangantu - Nisrinah Nadhilah (Eastasouth Journal of Effective Community Services, 2022)
Community empowerment is a process of Human Resource Development, but human resources have often become an obstacle to regional development, especially in coastal communities, karangantu coastal communities have community empowerment programs that make it a strategy that is quite helpful in the local community economy. Here the author uses a qualitative method of descriptive, with the results of research that Peel House is part of the change of the family economy, so they are not too dependent on the profits of fishermen catches.